2020
DOI: 10.18632/aging.102825
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide association study identifies genetic factors that modify age at onset in Machado-Joseph disease

Abstract: Machado-Joseph disease (MJD/SCA3) is the most common form of dominantly inherited ataxia worldwide. The disorder is caused by an expanded CAG repeat in the ATXN3 gene. Past studies have revealed that the length of the expansion partly explains the disease age at onset (AO) variability of MJD, which is confirmed in this study (Pearson's correlation coefficient R 2 = 0.62). Using a total of 786 MJD patients from five different geographical origins, a genome-wide association study (GWAS) was conducted to identify… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 42 publications
0
10
0
Order By: Relevance
“…The identification of genetic modifiers holds promise for modulating disease progression. The search for genetic modifiers of polyQ diseases has been actively carried out in the past 8‐13,35 . Most studies have provided only the genetic association without offering validation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The identification of genetic modifiers holds promise for modulating disease progression. The search for genetic modifiers of polyQ diseases has been actively carried out in the past 8‐13,35 . Most studies have provided only the genetic association without offering validation.…”
Section: Discussionmentioning
confidence: 99%
“…The search for genetic modifiers of polyQ diseases has been actively carried out in the past. [8][9][10][11][12][13]35 Most studies have provided only the genetic association without offering validation. With data obtained from cohorts of patients with HD and SCA3, we herein identify variants of 16 candidate genes that are associated with an AO LTA in both polyQ diseases.…”
Section: Discussionmentioning
confidence: 99%
“…As with other repeat expansion disorders (Depienne and Mandel 2021), measured repeat length is inversely correlated to age at onset accounting for ~ 55 to 60% of the variation in disease severity (de Mattos et al 2019;Akcimen et al 2020). The ATXN3 repeat is complex with the reference sequence (NM_004993.6) incorporating two synonymous glutamine-encoding CAA variants at positions three and six, and a nonsynonymous lysine-encoding AAG variant at position four i.e., (CAG)2(CAA)1(AAG)1(CAG)1(CAA)1(CAG)x (Kawaguchi et al 1994;Igarashi et al 1996) (Figure 1).…”
Section: Introductionmentioning
confidence: 75%
“…As with other repeat expansion disorders (Depienne and Mandel 2021), measured repeat length is inversely correlated to age at onset accounting for ∼ 55 to 60% of the variation in disease severity (de Mattos et al . 2019; Akcimen et al . 2020).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, GWAS Catalog database has reported that PQBP5/NOL10 was associated with cardiac troponin levels, arterial stiffness, waist circumference, and liver fibrosis, but not with polyQ diseases (https:// www.ebi.ac.uk/gwas/genes/NOL10), although it is unclear whether 46,231 human SNPs linked to PQBP5/NOL10 gene (https://www.ncbi. nlm.nih.gov/snp/?term=NOL10) have been examined in previous GWAS studies of polyQ diseases [35][36][37][38] . Expression profile databases such as Expression Atlas (https://www.ebi.ac.uk/gxa/home) have shown that PQBP5/NOL10 is widely distributed in human/mouse neural and nonneural cells, tissues, and organs.…”
mentioning
confidence: 99%